2016
DOI: 10.3386/w22670
|View full text |Cite
|
Sign up to set email alerts
|

Can Cash Transfers Help Households Escape an Inter-Generational Poverty Trap?

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
53
1
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 31 publications
7
53
1
7
Order By: Relevance
“…First, we add to the literature that studies the design and implementation of transfer programs (Baird et al, 2011, Barrera-Osorio et al, 2011, Glewwe and Muralidharan, 2016. Consistent with the results in previous studies (Baird et al, 2016, Araujo et al, 2016, Baez and Camacho, 2011, Akresh et al, 2013, we find that unconditional transfers do not lead to long term improvements in human capital outcomes. Second, we add to the literature that studies how micronutrient consumption -or lack thereof -in early life contributes to learning (Almond et al, 2011, Maluccio et al, 2009, Feyrer et al, 2017, Chong et al, 2016.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…First, we add to the literature that studies the design and implementation of transfer programs (Baird et al, 2011, Barrera-Osorio et al, 2011, Glewwe and Muralidharan, 2016. Consistent with the results in previous studies (Baird et al, 2016, Araujo et al, 2016, Baez and Camacho, 2011, Akresh et al, 2013, we find that unconditional transfers do not lead to long term improvements in human capital outcomes. Second, we add to the literature that studies how micronutrient consumption -or lack thereof -in early life contributes to learning (Almond et al, 2011, Maluccio et al, 2009, Feyrer et al, 2017, Chong et al, 2016.…”
Section: Introductionsupporting
confidence: 88%
“…In addition to addressing short-term needs, many transfer programs also aim to increase children's human capital as a means to improve lifetime outcomes and promote intergenerational mobility. Our paper contributes to the small and growing literature on the medium-and long-run impacts of transfer programs (Barham et al, 2019, Araujo et al, 2016, Millán et al, 2020 by studying the how unconditional cash and in-kind food transfers impacted the standardized test scores of primary school children in poor and remote areas of Mexico, 4 to 10 years after transfers were first received.…”
Section: Introductionmentioning
confidence: 95%
“…We also find support for this alternative to resettlement in the corpus of social policy, social justice and development literatures. Although not without contention (Carter et al, 2016;Araujo et al, 2017), viewed broadly, cash transfer programmes have been shown to reduce poverty, increase employment rates, and improve education and vaccination rates (Ballard, 2013;Ferguson, 2015;Hjelm et al, 2017). Here we see the potential of cash transfers to bolster the economic and social determinants of adaptive capacity and enable people to exercise their own agency in ways that state-driven planned resettlement projects with uneven outcomes cannot.…”
Section: Discussionmentioning
confidence: 97%
“…Most of the literature on CCTs and scholarships focuses on schooling and cognitive skill outcomes, with some exceptions that consider the impact of transfers on political and social factors, household consumption smoothing (Sparrow 2007), labor market outcomes (Araujo et al 2016;Filmer and Schady 2014;Parker and Vogl 2018;Silva and Sumarto 2015), or health (Cruz et al 2017). Few studies analyze the impacts on various outcome dimensions simultaneously.…”
Section: Socioemotional Outcomesmentioning
confidence: 99%